Memorandum of understanding between Unviersiti Teknologi MARA and Nurflix Productions Sdn Bhd / Fakulti Filem, Teater dan Animasi - Universiti Teknologi MARA, Fakulti Filem, Teater dan Animasi (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding on friendship and cooperation for friendship, cooperation and collaboration.